Activation of Toll-Like Receptors by Live Gram-Negative Bacterial Pathogens Reveals Mitigation of TLR4 Responses and Activation of TLR5 by Flagella - Amemiya, Kei; Dankmeyer, Jennifer L.; Bernhards, Robert C.; Fetterer, David P.; Waag, David M.; Worsham, Patricia L.; DeShazer, David (Frontiers in Cellular and Infection Microbiology, 2021)
Successful bacterial pathogens have evolved to avoid activating an innate immune system in the host that responds to the pathogen through distinct Toll-like receptors (TLRs). The general class of biochemical components that activate TLRs has been studied extensively, but less is known about how TLRs interact with the class of compounds that are still associated with the live pathogen. Accordingly, we examined the activation of surface assembled TLR 2, 4, and 5 with live Tier 1 Gram-negative pathogens that included Yersinia pestis (plague), Burkholderia mallei (glanders), Burkholderia pseudomallei (melioidosis), and Francisella tularensis (tularemia). We found that Y. pestis CO92 grown at 28 °C activated TLR2 and TLR4, but at 37 °C the pathogen activated primarily TLR2. Although B. mallei and B. pseudomallei are genetically related, the former microorganism activated predominately TLR4, while the latter activated predominately TLR2. The capsule of wild-type B. pseudomallei 1026b was found to mitigate the activation of TLR2 and TLR4 when compared to a capsule mutant. Live F. tularensis Schu S4 did not activate TLR2 or 4, although the less virulent F. tularensis LVS and F. novicida activated only TLR2. B. pseudomallei purified flagellin or flagella attached to the microorganism activated TLR5. Activation of TLR5 was abolished by an antibody to TLR5, or a mutation of fliC, or elimination of the pathogen by filtration. In conclusion, we have revealed new properties of the Gram-negative pathogens, and their interaction with TLRs of the host.